Synthesis of minimum control systems of hydraulic and pneumatic drives - Cherkashenko, M. V. (National Technical University "Kharkiv Polytechnic Institute", 2022)
The monograph presents the scientific direction developed by the author: "Synthesis of minimum of control systems of hydraulic and pneumatic drives", associated with topical problems of the modern theory of synthesis of drive s control systems, including theoretical foundations and methods of structural analysis and synthesis of d rive s control systems. Modern text material is of interest to professionals engaged in t he development of drive systems. Is intended for students in the study of relevant courses, as well as for raduate students of engineering speci alties.
Синтез мінімальних систем управління гідро- та пневмоприводов
Keywords: monograph; matrix logical function; undivided decomposition methods; synthesis minimal graph operations; discrete-analog systems control; standard positional structure; mathematical model